Usability testing and assessment of the Agro-Climatic Bulletin in Vietnam - Van, Lam Luong; Giraldo Mendez, Diana; Giles, James; Nguyen, Huong Mai; Le, Tam Thi; Swaans, Kees (2024)
This info note provides insights into the application of Human-Centred Design (HCD) in enhancing Agro-climatic Bulletin within the CGIAR Asian Mega-Deltas initiative. Since 2023, the HCD approach has been implemented in the Mekong River Delta, Vietnam, through direct engagement with farmers as end users. Key tools such as user personas, journey mapping, and usability testing have been employed to refine and improve the ACB. As part of a series, this info note highlights key results and lessons learned from applying HCD. Each note focuses on a specific tool within the process, providing practical insights for future applications.